Comparison of Ropivacaine 0.2% Alone and in Combination with Fentanyl for Caudal Anesthesia in Paediatric Patients - Grewal, Dr. Tejinderpal Kaur; Kaur, Dr. Balwinder; Kumar, Dr. Parmod; Kaur, Dr. Sukhdeep (International Journal of Innovative Research in Medical Science, 2019)
Background: Caudal epidural block is one of the most common regional techniques in paediatric anesthesia. It is safe, easy to perform and has been found to be very effective in children undergoing infra-umbilical surgeries .Ropivacaine produces differential neuraxial blockade with less motor block and reduced cardiovascular toxicity. Various adjuvants are added to increase the duration of action of local anesthetics. The aim of our study was to evaluate the action of fentanyl on duration of postoperative analgesia when added as an adjunct to ropivacaine in paediatric population of age 3-8 years undergoing infraumbilical surgeries. Methods: A double blind, prospective, comparative and randomized study was conducted on 50 paediatric patients undergoing elective infraumbilical surgery. Patients were randomly divided into two groups of 25 each by simple envelope method. After securing airway, caudal anaesthesia was given. Group R received 0.2% ropivacaine 0.5ml/kg and Group RF – received 0.2% ropivacaine 0.5ml/kg with fentanyl 0.5mcg/kg. Post-operative pain was assessed by face, legs, activity, cry and consolability pain assessment scale for 24 h. Duration of motor blockade and side effects were noted. The hemodynamics, duration of post-operative analgesia and number of rescue analgesia needed was noted and analyzed statistically. Results: Mean duration of analgesia in ropivacaine group is 441.60±102.29 minutes (7.35hrs) and in ropivacaine fentanyl group was 892±313.84 (14.86hrs). Statistically the difference was highly significant as p value was <0.001. Conclusions: Fentanyl as an adjuvant to ropivacaine for caudal block has significantly improved analgesic efficacy and increased the duration of post-operative analgesia in children undergoing infraumbilical surgery.